Thermophilic methane oxidation is widespread in Aotearoa-New Zealand geothermal fields - Houghton, Karen M.; Carere, Carlo R.; Stott, Matthew B.; McDonald, Ian R. (Frontiers in Microbiology, 2023)
Geothermal areas represent substantial point sources for greenhouse gas emissions such as methane. While it is known that methanotrophic microorganisms act as a biofilter, decreasing the efflux of methane in most soils to the atmosphere, the diversity and the extent to which methane is consumed by thermophilic microorganisms in geothermal ecosystems has not been widely explored. To determine the extent of biologically mediated methane oxidation at elevated temperatures, we set up 57 microcosms using soils from 14 Aotearoa-New Zealand geothermal fields and show that moderately thermophilic (> 40 °C) and thermophilic (> 60 °C) methane oxidation is common across the region. Methane oxidation was detected in 54 % (n=31) of the geothermal soil microcosms tested at temperatures up to 75 °C (pH 1.5-8.1), with oxidation rates ranging from 0.5 to 17.4 μmol g -1 d -1 wet weight. The abundance of known aerobic methanotrophs (up to 60.7 % Methylacidiphilum and 11.2 % Methylothermus) and putative anaerobic methanotrophs (up to 76.7 % Bathyarchaeota) provides some explanation for the rapid rates of methane oxidation observed in microcosms. However, not all methane oxidation was attributable to known taxa; in some methane-consuming microcosms we detected methanotroph taxa in conditions outside of their known temperature range for growth, and in other examples, we observed methane oxidation in the absence of known methanotrophs through 16S rRNA gene sequencing. Both of these observations suggest unidentified methane oxidizing microorganisms or undescribed methanotrophic syntrophic associations may also be present. Subsequent enrichment cultures from microcosms yielded communities not predicted by the original diversity studies and showed rates inconsistent with microcosms (> 24.5 μmol d -1 ), highlighting difficulties in culturing representative thermophilic methanotrophs. Finally, to determine the active methane oxidation processes, we attempted to elucidate metabolic pathways from two enrichment cultures actively oxidizing methane using metatranscriptomics. The most highly expressed genes in both enrichments (methane monooxygenases, methanol dehydrogenases and PqqA precursor peptides) were related to methanotrophs from Methylococcaceae, Methylocystaceae and Methylothermaceae. This is the first example of using metatranscriptomics to investigate methanotrophs from geothermal environments and gives insight into the metabolic pathways involved in thermophilic methanotrophy.